2013
DOI: 10.1021/jf401273n
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite PAAm/Methyl Cellulose/Montmorillonite Hydrogel: Evidence of Synergistic Effects for the Slow Release of Fertilizers

Abstract: In this work, we synthesized a novel series of hydrogels composed of polyacrylamide (PAAm), methylcellulose (MC), and calcic montmorillonite (MMt) appropriate for the controlled release of fertilizers, where the components presented a synergistic effect, giving very high fertilizer loading in their structure. The synthesized hydrogel was characterized in relation to morphological, hydrophilic, spectroscopic, structural, thermal, and kinetic properties. After those characterizations, the application potential w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(113 citation statements)
references
References 32 publications
9
100
0
4
Order By: Relevance
“…The investigation of the fertilizer release mechanism from hydrogel composite indicated that in this system the fertilizer nutrients release followed a Fickian diffusion type transport mechanism. Similar water-retaining and controlled-release fertilizers formulations have been reported in case of starch-based (Zhong et al 2013) and methyl cellulose-based (Bortolin et al 2013) formulations. Super absorbent polymer (SAP) in three levels, 0.15, 0.3, and 0.45 % have been mixed with sandy loam soil.…”
Section: +3supporting
confidence: 75%
“…The investigation of the fertilizer release mechanism from hydrogel composite indicated that in this system the fertilizer nutrients release followed a Fickian diffusion type transport mechanism. Similar water-retaining and controlled-release fertilizers formulations have been reported in case of starch-based (Zhong et al 2013) and methyl cellulose-based (Bortolin et al 2013) formulations. Super absorbent polymer (SAP) in three levels, 0.15, 0.3, and 0.45 % have been mixed with sandy loam soil.…”
Section: +3supporting
confidence: 75%
“…This showed that the castor oil PU based coatings were better able to retain/release macronutrients. These comparisons between the curves and the release behavior were interpreted from a model modified from that suggested by Peppas to obtain the release process kinetic parameters 26 :…”
Section: Resultsmentioning
confidence: 99%
“…WA [52], SR [53], EWC [29] are essential features for the SRF. The results of experiment for NZ and ZNC for all these three parameters are 49, 63%; 3.28, 3.53 g/g and 76.63, 77.92%, respectively.…”
Section: Salt Index (Si)mentioning
confidence: 99%